UNIT 9.6 In Vitro Selection Using Modified or Unnatural Nucleotides. Issue 1 (26th March 2014) - Stovall, Gwendolyn M.; Bedenbaugh, Robert S.; Singh, Shruti; Meyer, Adam J.; Hatala, Paul J.; Ellington, Andrew D.; Hall, Bradley
Abstract: Incorporation of modified nucleotides into in vitro RNA or DNA selections offers many potential advantages, such as the increased stability of selected nucleic acids against nuclease degradation, improved affinities, expanded chemical functionality, and increased library diversity. This unit provides useful information and protocols for in vitro selection using modified nucleotides. It includes a discussion of when to use modified nucleotides; protocols for evaluating and optimizing transcription reactions, as well as confirming the incorporation of the modified nucleotides; protocols for evaluating modified nucleotide transcripts as template in reverse transcription reactions; protocols for the evaluation of the fidelity of modified nucleotides in the replication and the regeneration of the pool; and a protocol to compare modified nucleotide pools and selection conditions. Curr. Protoc. Nucleic Acid Chem . 56:9.6.1‐9.6.33. © 2014 by John Wiley & Sons, Inc.